EURYCINOID: POTENSI RUMPUT GONG (EURYCAULON CINEREUM) KHAS BANGKA BELITUNG SEBAGAI KANDIDAT SENYAWA ANTIKANKER PAYUDARA BERBASIS BAHAN ALAM - Dian Nida Salsabila; Asgar Purnama; Yoga Febriana; Hady Anshory; Arde Toga Nugraha (Universitas Islam Indonesia, 2020)
Traditionally, some People from bangka belitung has consumed Eriocaulon cinereum R.Br as an anticancer drug. Aims of this study is to determine the potential of cytotoxicity of Fraction of Ethyl Acetate and Dichlorometane against T47D cell. Fractionation using Vacuum Liquid Chromatography (VLC) method. MTT assay method was used on evaluating the citotoxic activity. The fraction of dichloromethane performed high activity as a chemopreventive agent with IC50 score was 131,921 µg/ml to T47D and 413,042 µg/ml cells to vero cell whereas for ethyl acetate fraction performed lower activity as chemopreventive agent with IC50 score was 531,808 µg/ml to T47D and 679,114 µg/ml to vero cell). Phytochemical tests showed that the dichloromethane fraction contains phenolic, steroid and terpenoid compounds. While ethyl acetate fraction contains alkaloids, flavonoids and terpenoids. These compounds have activity on cancer cells through apoptotic mechanisms. The results showed the excellent potential of this plant in killing breast cancer cells.